Urbanization Impacts Top Predators and Alters Biotic Interactions in Predator–Prey–Mutualistic Communities of Urban Dry Grasslands - Tanja M. Straka; Viktoriia Radchuk; Ingo Kowarik; Moritz von derLippe; Sascha Buchholz (Ecology and Evolution)
ABSTRACT Urbanization as a major driver of global change modifies biodiversity patterns and the abundance and interactions among species or functional species groups. For example, urbanization can negatively impact both predator–prey and mutualistic relationships. However, empirical studies on how urbanization modifies biotic, particularly multitrophic, interactions are still limited. In this study, we applied a framework focused on a predator–prey–mutualistic relationship involving communities of insect‐pollinated vascular plants, pollinators (bees and hoverflies), predatory spiders, and sand lizards as top predators to test (i) the effect of urbanization on abundance and species richness at different trophic levels and (ii) the effect of urbanization on the regulation of biotic interactions using correlations between species abundances as a proxy. By assessing 56 dry grassland patches in Berlin, Germany, we found that higher trophic levels (sand lizard abundance as well as predatory spider species richness and abundance) were significantly impacted by urbanization whereas pollinators were affected to a lesser degree (only abundance, but not species richness). In contrast, insect‐pollinated vascular plants were not impacted by urbanization. Path analyses revealed significant relationships in low‐urbanized areas. In these areas, we observed significant bottom‐up‐regulated mutualistic and predator–prey interactions (plants–pollinators, and pollinators–predatory spiders), as well as top‐down‐regulated predator–prey interactions (sand lizards–pollinators, and predatory spiders–pollinators). In contrast, no significant interactions were found in highly urbanized sites. Our results suggest that bottom‐up regulation is stronger than top‐down regulation in low‐urbanized areas. To our knowledge, this is the first study to examine the effects of urbanization on predator–prey–mutualistic interactions and to determine whether these interactions are regulated by bottom‐up or top‐down processes. These findings enhance our understanding of multitrophic interactions in urban environments and their associated ecosystem services, such as pollination, thereby supporting efforts in urban biodiversity conservation.